1994
DOI: 10.1136/jnnp.57.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits in progressive supranuclear palsy, Parkinson's disease, and multiple system atrophy in tests sensitive to frontal lobe dysfunction.

Abstract: Groups of patients with idiopathic Parkinson's disease, multiple system atrophy, and progressive supranuclear palsy or Steele-Richardson-Olszewski syndrome, matched for overall clinical disability, were compared using three computerised cognitive tests previously shown to be sensitive to frontal lobe dysfunction. On a test of planning based on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
145
0
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(164 citation statements)
references
References 40 publications
13
145
0
6
Order By: Relevance
“…However, it is difficult to pinpoint the site of action for clonidine to impair speed of effortful processing, though it may involve the temporal lobe, and areas of the "fronto-striatal" loops at the cortical and basal ganglia levels (Lange et al 1992;Owen et al 1993;Robbins et al 1994). First, 5 g/kg clonidine had no effect on the accuracy of ID/ED test but slowed responding at the ED stage, a finding mimicking closely the defect induced by temporal excision in humans (Owen et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to pinpoint the site of action for clonidine to impair speed of effortful processing, though it may involve the temporal lobe, and areas of the "fronto-striatal" loops at the cortical and basal ganglia levels (Lange et al 1992;Owen et al 1993;Robbins et al 1994). First, 5 g/kg clonidine had no effect on the accuracy of ID/ED test but slowed responding at the ED stage, a finding mimicking closely the defect induced by temporal excision in humans (Owen et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Defective executive functions, such as planning, working memory and attentional set-shifting, are characteristic features of several neurological disorders including Alzheimer disease, frontal lobe dementia, and basal ganglia disorders (Sahakian and Owen 1992;Robbins et al 1994;Coull et al 1996). Previous evidence has suggested that the prefrontal cortex is involved in the modulation of executive functions, and that dysfunction of this region may result in specific cognitive defects (Luria 1969;Owen et al 1990Owen et al , 1995.…”
mentioning
confidence: 99%
“…Rather, it is likely that a threshold in white matter lesion load exists, beyond which cognitive decline is caused, and that this threshold can vary depending on host factors and the presence of concomitant lesions [23]. Although cognitive dysfunction represents an exclusion criterion in the diagnosis of MSA, several studies reported frontal lobe-associated cognitive dysfunction in patients with MSA, by means of comprehensive neuropsychological testing [26,27]. Pathological studies evaluating neuronal morphology in detail and distribution of GCIs have provided evidence of cortical involvement especially in the frontal cortex and its associated white matter as well as in the striatum of patients with MSA, suggesting that GCIs in these areas may contribute to cognitive deficits [15,24].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the behavioural problems of patients with PD, Huntington's disease (HD), and dystonia and the nature of their involuntary movements has been extensively documented. As a result of these observations it has been suggested that the basal ganglia may play a role in determining the force and velocity of movement (Hallett & Khoshbin, 1980 ;Anderson & Horak, 1985), preparing for movement (Schultz & Romo, 1988 ;Kimura, 1990), selecting motor programs (Brotchie et al 1991), enabling movements to become automatic (Brotchie et al 1991), facilitating sequential movement (Marsden, 1987 ;Kimura, 1990 ;Brotchie et al 1991 inhibiting unwanted movements (Penney & Young, 1983 ;Mink & Thach, 1991), alerting animals to the presence of novel or rewarding circumstances (Brown & Marsden, 1990 ;Ljungberg et al 1992 ;Schultz, 1992), and mediating selective attention (Wichman & DeLong, 1999) and conditional learning and planning (Taylor et al 1986 ;Gotham et al 1988 ;Robbins et al 1994). The basal ganglia, however, clearly do not act in isolation but are part of a system of parallel distributed corticosubcortical loops.…”
Section: mentioning
confidence: 99%